Implementasi Kurikulum 2013 dalam Pembelajaran Sejarah di Sekolah Menengah Atas Negeri 106 Jakarta Timur - Febta Pratama; Arief Hidayat (Tsaqofah, 2019)
SMA Negeri 106 Jakarta is a school designated by the government as the first school to implement the 2013 curriculum. This study aims to see and describe the implementation of the 2013 curriculum in learning, how the form of acceptance, school readiness, and the obstacles faced in implementing the curriculum. This research uses qualitative research methods, with a case study in the school of SMAN 106 Jakarta. Data analysis was carried out by technical data analysis according to Miles and Hubberman with three stages, namely data reduction, data display, and data verification. The results show that the 2013 curriculum has been implemented since the beginning at SMAN 106 Jakarta. History subjects are among the subjects that first apply the 2013 curriculum in the learning process. The learning methods taught have used the Scientific and Discovery methods. The implementation of the 2013 curriculum can be seen in the learning tools that are in accordance with the provisions of the central government. The obstacles faced in implementing the 2013 curriculum are technical constraints related to learning resources and facilities and infrastructure.